ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN VIDEO INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN GEDONG DALEM 03 KOTA CILEGON - Supendi; M.Pd., Beni Junedi; S.Pd., M.Pd.T. , Ade Fricticarani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to increase students' interest and motivation to learn and make it easier to understand abstract or difficult learning material concepts that can be visualized through interactive videos, increasing students' active involvement in the learning process. The subjects in this research were fifth grade students at SDN Gedong Dalem 03, the principal, teacher council and experts in the field of education. The method in this research uses qualitative research methods and data collection is used in the form of qualitative data which includes observation data, interviews, questionna-ires, and photos of implementation activities. The collected data is then analyzed to formulate results based on the assessment. Assessment by experts = 88.0%, by class teachers = 85.6%, students regarding interactive video learning media = 91.7%, limited group trials from ten respondents = 93.8%, from the results of the student response questionnaire on field test = 87.8%. The analysis results are acumulated with the criteria